Perkawinan Beda Agama dan Pemberian Dispensasi dalam Gereja Katolik (Tinjauan Kasus di Paroki St. Maria Ratu Rosari-Reo Keuskupan Ruteng) - Efim, Alfederikus; Endi, Yohanes (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
Abstract The focus of this paper is to discuss the case of interfaith marriage in the area of St. Maria Ratu Rosari-Reo Parish, Ruteng Diocese, especially in the context of the view of canon law of the Catholic Church. This article investigates the implications of canon law related to interfaith marriage cases and the process of granting dispensation to Catholics involved. The author analyzes the theological, ethical, and canonical legal foundations involved in handling cases of this kind. In addition, this paper also discusses the social and spiritual impact of the dispensation decision on the individuals and Catholic communities involved. The case of interfaith marriage in the parish of St. Mary Queen Rosari-Reo highlights the complexity of the canon law of the Catholic Church. The theological, ethical, and procedural foundations of canon law are analyzed, while the social and spiritual impact of dispensation decisions is considered. The importance of integrating the principles of Church teaching with the social and pastoral reality of Catholics is highlighted in the context of interfaith marriages in the Parish of Str. Maria Ratu Rosari-Reo Ruteng Diocese.